2022
DOI: 10.1002/lsm.23594
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the safety and efficacy of low fluence Q‐switched 1064‐nm and conventional Q‐Switched 755‐nm lasers in the treatment of café‐au‐lait macules: A prospective self‐controlled trial

Abstract: Background Conventional high fluence Q‐switched (HFQS) Alexandrite 755‐nm are widely used in clinical café‐au‐lait macules (CALMs) treatment. There have been recent concerns regarding the efficacy and safety of low fluence Q‐switched (LFQS) Nd: YAG 1064‐nm lasers. Objective To evaluate the efficacy and safety of the conventional HFQS and LFQS laser in the treatment of CALMs. Methods Within 3 months, 20 patients underwent prospective self‐controlled split‐lesion treatments with HFQS once or twice depending on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Te LFQS laser had obvious lesion clearance after the frst treatment. While both research studies indicated with the increase of LF-QSNY treatment sessions, the clearance of lesions gradually accumulated [26].…”
Section: Discussionmentioning
confidence: 91%
“…Te LFQS laser had obvious lesion clearance after the frst treatment. While both research studies indicated with the increase of LF-QSNY treatment sessions, the clearance of lesions gradually accumulated [26].…”
Section: Discussionmentioning
confidence: 91%
“…Typically, the Q-switched laser pulses meet the stress confinement (i.e., isochoric heat deposition) in that the pulse duration is shorter than the stress relaxation time (1 μs) [8]. Because of instant heat deposition upon volumetric light absorption in a target, the Q-switched laser system has been applied in various fields, such as micromachining, scaffold fabrication, and laser-tissue resection [9][10][11]. However, a single pulse with a high peak power often causes undesirable damage to optical components and target materials [12].…”
Section: Introductionmentioning
confidence: 99%
“…Several irradiation methods have been developed to minimize thermomechanical damage by reducing the peak power of each pulse. For example, Q-switched pulses with low-pulse energies (<1 mJ) at high-repetition rates (a few hundred kHz) have been applied for laser micromachining [9,10]. The application of the multiple Q-switch pulses can minimize the excessive accumulation of thermal stress but can maintain the ablation performance during the micromachining process.…”
Section: Introductionmentioning
confidence: 99%